2015
DOI: 10.1177/2158244015606491
|View full text |Cite
|
Sign up to set email alerts
|

Media Priming of Road Traffic Accidents in Kenya

Abstract: This article examines how the print media in Kenya reported road traffic accidents (RTAs). Using the priming theory, the article sought to identify the patterns of reporting and issues arising from such reporting of RTAs in the print media in Kenya. This is because the cost of RTAs in Kenya to the economy is estimated at Ksh. 14 billion per year. The study was a content analysis of two leading newspapers in Kenya-Daily Nation and the Standard newspapers. Data were collected using an analysis of the stories con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Reporters are likely to sensationalize and over-emphasize traffic crash stories, rarely mentioning the possible causes of the crash ( 6 , 7 ). News reports often include information on the vehicle type involved in the crash but rarely report on the characteristics of the people injured and vehicles damaged ( 8 , 10 ). An analysis conducted on Ghanaian newspapers reveals that only 22% of articles cover pedestrian injuries, which account for 50% of the traffic fatalities in Ghana ( 8 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reporters are likely to sensationalize and over-emphasize traffic crash stories, rarely mentioning the possible causes of the crash ( 6 , 7 ). News reports often include information on the vehicle type involved in the crash but rarely report on the characteristics of the people injured and vehicles damaged ( 8 , 10 ). An analysis conducted on Ghanaian newspapers reveals that only 22% of articles cover pedestrian injuries, which account for 50% of the traffic fatalities in Ghana ( 8 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The country relies majorly on public service vehicles (PSVs) to meet the commuter needs of diverse groups of people. It has been reported that mode of public transport (Matatu industry) in Kenya is at fault when it comes to issues on safety (Manyara, 2016) (Mogambi & Nyakeri, 2015). PSVs in Kenya are legalized to carry between 10 and 50 passengers depending on the category of the vehicle (R. of K. (GoK), 2018).…”
Section: Public Service Vehicles and Motorbikesmentioning
confidence: 99%
“…In several papers, it is reported that 85% of the accidents are caused by driver error in Kenya ranging from over speeding, intoxication and/or plain recklessness among others (Manyara, 2016), (Mogambi & Nyakeri, 2015). The Kenya police in conjunction with NTSA has been enforcing adherence of traffic rules in the country.…”
Section: Policingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that Kenya has one of the highest road fatality rates in relation to vehicle ownership in the world, with an average of 7 deaths from the 35 road crashes that occur each day (Odero, Meleckidzedek & Heda, 2003). Kenya loses nearly 3000 persons due to roads accidents annually which translates to approximately 68 deaths per 10,000 registered vehicles, which is higher (30-40 times greater) than in highly motorized countries (Mogambi & Nyakeri, 2015).…”
mentioning
confidence: 99%